L’anthropologie juridique au milieu du gué : Crise idéologique ou crise épistémologique ? - Jean-Pierre Allinne (Clio@Themis)
This paper would like to underline the current methodological crisis into anthropology, and specially into judicial anthropology. But this crisis opens in the same time new sights on representations of justice through local and individual analysis. For that reason, it is divided in two parts : the first one deals with the calling into question of great macro-explanations of society (marxist as well as structuralist) and its consequences into the judicial methodology. The second part underlines the rise of micro historian and a culturalist approach of society. It aims to show the wealth of micro-history of trials and of customs for a new approach of legal history.